The Impact of Government Incentives on Electric Vehicle Adoption in the Metropolitan Jakarta Area - Albert Hasudungan; Billy Tandean; Edrick Aurelius; Redha Widarsyah; I Kadek Dian Sutrisna Artha (Jurnal Ekonomi Pembangunan, 2023)
This study investigates the effect of government economic incentives on electric vehicles (EV) in the metropolitan Jakarta area (Jakarta, Bogor, Depok, Tangerang, Bekasi). A survey was collected from 121 prospective and current EV users in Jakarta and its neighboring regions area. The collection was then analyzed using logistic regression. The research finds that EV subsidy, EV infrastructure, EV tax deduction, and age have significant effects on EV adoption. According to this stance, higher EV subsidy propels more EV adoption. In addition, respondents significantly consider the availability of EV infrastructure for EV adoption. Our study also reveals that the younger the age, the higher the preference for EV adoption. Furthermore, the lower the tax deduction, the increasing adoption of electric vehicles. Those variables are important factors to amplify EV adoption among our research respondents. This study implies that potential consumers are aware of and react positively to policy efforts to reduce upfront and maintenance costs for the transition to EV cars in the metropolitan Jakarta area.